Limitations of COVID-19 testing and case data for evidence-informed health policy and practice - Elizabeth Alvarez; Iwona A. Bielska; Stephanie Hopkins; Ahmed A. Belal; Donna M. Goldstein; Jean Slick; Sureka Pavalagantharajah; Anna Wynfield; Shruthi Dakey; Marie-Carmel Gedeon; Edris Alam; Katrina Bouzanis (BMC, 2023)
Abstract Background Coronavirus disease 2019 (COVID-19) became a pandemic within a matter of months. Analysing the first year of the pandemic, data and surveillance gaps have subsequently surfaced. Yet, policy decisions and public trust in their country's strategies in combating COVID-19 rely on case numbers, death numbers and other unfamiliar metrics. There are many limitations on COVID-19 case counts internationally, which make cross-country comparisons of raw data and policy responses difficult. Purpose and conclusions This paper presents and describes steps in the testing and reporting process, with examples from a number of countries of barriers encountered in each step, all of which create an undercount of COVID-19 cases. This work raises factors to consider in COVID-19 data and provides recommendations to inform the current situation with COVID-19 as well as issues to be aware of in future pandemics.